Pacing strategies during male 1500 m running world record performances - Casado, A.; García-Manso, J. M.; Romero-Franco, N.; Martínez-Patiño, M. J. (Research in Sports Medicine, 2021)
The aim was to determine the pacing strategies used to achieve male 1500 m running world record performances. Lap times (three first laps and the last 300 m) for the last 37 male 1500 m world record performances achieved since 1917 until 1998 were collected. An analysis of variance with repeated measures and a Bonferroni post hoc test were conducted to determine differences between the percentages of race average speed at each lap. Lap 1 and last 300 m differed from lap 2 and 3, being the latter slower (P <0.001, 1.44 =ES = 1.95), and displaying a U-shaped pacing profile. Whereas the pacing strategies observed differed from those previously determined for major championship races, a fast endspurt was always present and therefore athletes aiming for a world standard performance should train for developing their anaerobic capacity in addition to a high aerobic power.